1992
DOI: 10.1037/h0088248
|View full text |Cite
|
Sign up to set email alerts
|

Developing school-based consultation teams: A design for organizational change.

Abstract: The process of altering how school-based services are conceptualized and delivered is discussed relative to the literature on effective change and innovation implementation. The development of the Instructional Consultation Team model is described, and a model for change consisting of three stages-initiation, implementation, and institutionalization-is presented to guide dissemination and utilization of the model. Particular emphasis is given to the importance of conducting relevant evaluations at each stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
(19 reference statements)
1
30
0
Order By: Relevance
“…An alternative proposal for the use of teams to alter how school-based services are conceptualized and delivered has been articulated by Rosenfield (1992). Rosenfield suggests the implementation of interdisciplinary instrucfional consulration ream (fC-Team).…”
Section: Changes In Formal Organizationmentioning
confidence: 99%
“…An alternative proposal for the use of teams to alter how school-based services are conceptualized and delivered has been articulated by Rosenfield (1992). Rosenfield suggests the implementation of interdisciplinary instrucfional consulration ream (fC-Team).…”
Section: Changes In Formal Organizationmentioning
confidence: 99%
“…While there are potential benefits to a small fixed menu of effective interventions for consultees to implement, packaged approaches have been found to be inflexible (Rosenfield, 1992). It is important that resources provide adequate choice for consultees.…”
Section: Prepared Intervention ''Packages'' For Commonly Occurring Stmentioning
confidence: 99%
“…The software would provide prompts for the type of information that should be shared at the meeting, and keep the meeting focused on a positive solution for the student. While several authors have discussed the importance of a collaborative free exchange of ideas (Conoley & Conoley, 1982;Rosenfield, 1992), little empirical information has been gathered about aspects of the consultation process that lead to optimal student outcomes. It has been suggested that in the spirit of collaboration and trust, data driven decision making and accountability has been sacrificed (Witt, 1997).…”
Section: Rationale For Team Consultation Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…The improved quality of student products for both identified and unidentified students supports the educational benefits of this approach. Overall, the school system was enhanced by resource and cost efficiency (Knoff, & Batsche, 1991), improvement in student and teacher behaviors and expanded roles for the school system (Graden, Casy, & Bonstom, 1985), high expectations from teachers (Curtis & Meyers, 1985), positive teacher attitudes (Kratochwill & Van Someren, 1985), and enhancement of student social and academic success (Idol, 1989;Jason & Perone, 1978;Knoff & Batsche, 1991;Rosenfield, 1992). In general, the research base on consultation consists of studies of the consultative process, staff development, effectiveness of models, teacher competencies, and proficiency of consultees (Dettmer, Thurston, & Dyck, 1993).…”
Section: A Resource Consultation Model In Gifted Educationmentioning
confidence: 99%